Lessons from exceptional school leaders - Goldberg, Mark F., 1938- (Association for Supervision and Curriculum Development, 2001)
Ernest Boyer pushed school leaders to close "the gap between the haves and have-nots." Al Shanker led teachers to form a strong union. Deborah Meier created small schools of choice that broke achievement records. Martin Brooks has made staff development a hallmark of his administrative work for over 20 years. Through interviews with these and many other outstanding school leaders, Mark Goldberg has distilled the essence of effective school and district leadership. You'll learn how strong leaders . Form beliefs about school excellence. . Support a strong staff development program. . Broaden the school or district leadership. . Adapt leadership skills to specific school or district needs. . Address the gaps caused by discrimination, racism, and poverty. You'll also find out how to encourage other educators to become leaders and to build teams, work groups, and community support networks. This is an essential guide for anyone who wants to know how to start--and maintain--an innovative educational program that supports high student achievement. Mark Goldberg has more than 30 years' experience as a teacher, a school administrator, and an education journalist. He is a senior editor for Corwin Press and an educational consultant